Sustainable Place Branding and Visitors’ Responses: A Systematic Literature Review - Liasidou, Sotiroula; Garanti, Zanete; Ilkhanizadeh, Shiva (My University, 2024)
Admittedly, tourism stakeholders become more aware of the negative impacts of tourism, and it has become increasingly important to brand and position destinations towards sustainability. The main concern is emphasizing economic, social, and environmental awareness and implementation at the destination level regarding planning and development. This paper identifies the importance of sustainable place branding as part of destination social responsibility in the current global context. The main focus is identifying visitors’ responses as part of sustainable destination marketing. The study conducts a systematic literature review by rigorously selecting 26 related articles from the 106 search results for further analysis. The study results highlight the emergence of sustainable place branding concepts in academic literature, especially after the post-pandemic period. The themes identified in the literature analysis revolve around sustainable place branding in creating unique tourism experiences and engagement that resonates with the visitors’ self-perceptions and expectations of a destination. Sustainable place branding positively impacts destination image, trust, value, and loyalty. Moreover, it can create positive visitor outcomes, such as an intention to revisit because of positive word of mouth. The article concludes with suggestions for future research, emphasizing the need to explore further sustainable place branding and its influence on visitors’ responses in the evolving landscape of global tourism.
Keywords: destinations; place branding; social responsibility; sustainability; systematic review